Palestinian Resident Doctors’ Job Satisfaction and Quality of Working Life in the West Bank Hospitals - Saleh, Mohanad; Misk, Rami A; Alzughayyar, Tareq Z (My University, 2019)
Introduction: Resident doctors play an important role in hospital care, working under difficult situations of sleep deprivation and work, a 47-item questionnaire regarding job satisfaction was formulated based on a Canadian doctor feedback questionnaire, the new questionnaire was reviewed by 5 experts, and was completed twice by 10 residents for reliability check. 296 questionnaires were distributed on residents across the five hospitals affiliated with the Palestinian Medical Council. For data analysis SPSS ver.17 was used. Results: 186 residents completed the questionnaire with 62.8% response rate. The quality of working life and overall satisfaction was high in 31.1%, moderate in 50.6%, and low in 15.3% of sample. The younger population had increased overall job satisfaction. Number of on call night shifts and salary had inverse relation with overall job satisfaction, Palestinian medical complex of Ramallah had the highest overall job satisfaction, and lowest at Hebron Governmental hospital. Conclusion: Job satisfaction was high to moderate in majority of resident doctors with effect of demographic and work variables
Keywords: Research Subject Categories::MEDICINE; public health; Resident doctors